Development of phenol-grafted polyglucuronic acid and its application to extrusion-based bioprinting inks. (1st February 2022) - Sakai, Shinji; Kotani, Takashi; Harada, Ryohei; Goto, Ryota; Morita, Takahiro; Bouissil, Soukaina; Dubessay, Pascal; Pierre, Guillaume; Michaud, Philippe; El Boutachfaiti, Redouan; Nakahata, Masaki; Kojima, Masaru; et al.
Abstract: In this present work, we developed a phenol grafted polyglucuronic acid (PGU) and investigated the usefulness in tissue engineering field by using this derivative as a bioink component allowing gelation in extrusion-based 3D bioprinting. The PGU derivative was obtained by conjugating with tyramine, and the aqueous solution of the derivative was curable through a horseradish peroxidase (HRP)-catalyzed reaction. From 2.0 w/v% solution of the derivative containing 5 U/mL HRP, hydrogel constructs were successfully obtained with a good shape fidelity to blueprints. Mouse fibroblasts and human hepatoma cells enclosed in the printed constructs showed about 95% viability the day after printing and survived for 11 days of study without a remarkable decrease in viability. These results demonstrate the great potential of the PGU derivative in tissue engineering field especially as an ink component of extrusion-based 3D bioprinting.